Sleep in Habitual Adult Video Gamers: A Systematic Review - Kemp, Chadley; Pienaar, Paula R.; Rosslee, Dominique T.; Lipinska, Gosia; Roden, Laura C.; Rae, Dale E. (Frontiers in Neuroscience, 2021)
Video gaming is a popular, globally recognized phenomenon, played recreationally or competitively as esports. Gaming is a typically sedentary nighttime activity; therefore, the potential to impact sleep and health is high. Furthermore, there are limited studies on adult gamers, who represent the majority demographic in esports. This review examines evidence describing sleep in habitual adult gamers to understand the associated risk for cardiometabolic disease or the benefits to gaming performance. Three electronic databases (PubMed, Scopus, ISI Web of Science) were searched for peer-reviewed articles published between January 2000 - April 2020. Twelve studies reporting on sleep in habitual adult gamers were included. A narrative synthesis was employed to report results, owing to high levels of heterogeneity across the included studies. Gamers with higher gaming addiction scores were more likely to have shorter, poorer quality sleep and greater daytime sleepiness and insomnia scores than gamers with lower gaming addiction scores and non-gamers. In addition, high-volume gamers were more likely to have worsened sleep quantity and quality, with delayed sleep timing and increased prevalence of insomnia. Despite limitations in the design of the included studies, excessive gaming is broadly associated with worsened sleep parameters. Noteworthy is the lack of studies investigating cardiometabolic health in gamers. Future work should explore the relative contribution and associated risk that various games, genres, and timing of gaming activities have on sleep, physical and mental health, particularly in vulnerable gaming cohorts engaged with contemporary forms of gaming and esports.